Future prospect for Islamic education in commonwealth independent states: a historical perspective and a blueprint for the development of Islamic educational institutions - Ashurov, Sharofiddin; Mohammad, Habibullah (2019)
Islam has been widely practiced in the Commonwealth of Independent States (CIS) since the be-ginning of Islamic history and it was a center of excellence for Islamic education from as early as the eighth century, as part of the Muslim conquest territory from Samarkand to Bukhara. The aim of this paper is to explore the obscure history of Islamic education and civilization in the CIS coun-tries with special focus on Central Asia. The inductive method was applied to examine data from secondary sources for this qualitative study which focused on how the CIS countries could make remarkable progress in the future to develop Islamic educational institutions and produce Islamic intellectuals which will have a positive impact on the development of future Muslim generations in this region. The explorative results showed that Islamic education is among the major factors of so-cial stability in the CIS region and it takes into account the expectations of people in order to build peaceful, knowledge-based and prosperous societies. Moreover, it is recommended to authorities in the CIS region to pay special attention to developing Islamic education institutions that will lead to improvements in educational relations between the CIS region and the different OIC nations which will eliminate the disputes among the CIS nations regarding enhancing harmony and he-gemony.